Etiology of parapneumonic effusion and pleural empyema in children. The role of conventional and molecular microbiological tests. (July 2016) - Krenke, Katarzyna; Sadowy, Ewa; Podsiadły, Edyta; Hryniewicz, Waleria; Demkow, Urszula; Kulus, Marek
Abstract: Background: An increasing incidence of parapneumonic effusion and pleural empyema (PPE/PE) has been reported in recent studies. As only few data on etiology of PPE/PE in Central Europe have been reported, we undertook a study on the etiology of PPE/PE in children, using both standard culture and molecular techniques. Methods: This prospective study was conducted between June 2011 and December 2013. Consecutive children with PPE/PE complicating community acquired pneumonia, who required diagnostic/therapeutic thoracentesis were included. Blood and pleural fluid samples for microbiological cultures were collected. Molecular methods were applied to identify Streptococcus pneumonia, Haemophilus influenzae, Staphylococcus aureus, Streptococcus pyogenes, Mycoplasma pneumoniae, Chlamydophila pneumoniae, and respiratory viruses in pleural fluid. Results: The study group included 64 children, median age 4 (1–15). Seven of 64 (10.9%) blood cultures and 11 of 64 (17.2%) pleural fluid cultures revealed bacterial growth. The most common bacteria detected was S. pneumoniae (13 blood and pleural fluid samples from 11/64 (17.2%) children). DNA sequences of typical bacteria were found in 29/64 (45.3%) pleural fluid samples. S. pneumoniae was identified in 90% of these samples. The most common serotypes were: serotype 6B in 9/26 (36.6%), 19A in 6/26 (23%), serotype 3 in 3/26 (11.5%), 6A and 23F (both in 2/26 i.e. 7.7%) patients. Molecular methods identified atypical bacteria in 8/58 (13.8%) and respiratory viruses in 12/58 (20.7%) pleural fluid samples. Conclusions: S. pneumoniae, in particular serotype 6B and 19A, is the most common etiologic agent of PPE/PE in Polish children. The use of PCR significantly improves pathogen identification in pleural fluid. Highlights: Pleural empyema is challenging complication of childhood community acquired pneumonia. S. pneumoniae is the most common pathogen responsible for pleural empyema in children. Serotypes 6B and 19A were most commonly identified as causative pathogens. The use of PCR improves the efficacy of pathogen identification in pleural fluid. Molecular methods can help to detect atypical bacteria and viruses in pleural fluid.